MC11: A new opportunity to reduce distortions in the global agricultural trade system - Laborde Debucquet, David; Piñeiro, Valeria; Glauber, Joseph W. (2017)
The Eleventh Ministerial Conference (MC11) of the World Trade Organization (WTO) will take place from 10 to 13 December 2017 in Buenos Aires, Argentina. The Ministerial Conference which is attended by trade ministers and other senior officials from the organization’s 164 members, is the highest decision-making body of the WTO. The last Ministerial Conference was held in Nairobi, Kenya in December 2015. This will be the first Ministerial Conference to be held in South America and will provide an opportunity to reduce trade barriers and further liberalize the global trading system.